Epidemiologia da Hanseníase na Paraíba e sua relação com a cobertura da Atenção Primária à Saúde e condições socioeconômicas - Kleane Maria da Fonseca Azevedo Araújo (2018)
Leprosy is a curable disease of high significance, given to physical disabilities from the untreated problem. It remains a public health problem in several countries. Socially determined, it overcomes the biological barriers, being fundamental to understand its occurrence in different contexts. The aim of this study is to assess the epidemiology of leprosy and its relationship with the coverage of Primary Health Care and socio-economic conditions in the State of Paraiba, in the period from 2001 to 2016. This mixed ecological study of multiple groups and time series has the municipalities as unit of analysis. Leprosy data were used and of the System of Information of Reportable Diseases. Trend analysis was performed by generalized linear regression by the Prais Winsten indicators: annual detection rate of new cases of leprosy in the general population and in children under 15; rate and proportion of cases diagnosed with grade 2 physical disability. We analyzed the spatial distribution of risk for illness by leprosy, through an index formed by epidemiological indicators that ranked the municipalities in high, medium, low, and very low risk. It was found that the ratio of the coverage of Primary Health Care and Municipal Human Development Index with the leprosy epidemiological indicators for Poisson regression with zeros inflation. There were analyzed 12,134 new cases of leprosy. It was observed in Paraiba downward trend for overall detection rate (-4.8%), in children under 15 (-6.7%) and stationary for rate (-2.1%) and proportion (2.7%) of cases diagnosed with grade 2 of physical disability. It should be noted that the trend of these indicators is heterogeneous among the macro-regions of health in the State, only the fourth macro-region presents reduced magnitude of endemy. The spatial distribution is different in the State of Paraiba territory; it presents high-risk clusters in the Eastern and Western regions of the State with time reduction in the Western region. The increase in the coverage of the Family Health Strategy has contributed significantly to increase the detection rate in the general population, but did not show relationship with the detection in children under 15 and grade rate 2 of disability. The improvement of the Municipal Human Development Index contributed to increased cases of the disease in the general population and reduction in children under 15. Leprosy presents itself in decline in Paraiba; however, it is evidenced that diagnoses occur late and the transmission remains active. Although there has been an increase in the coverage of health services and Municipal Human Development Indexes, and this has influenced the improvement of leprosy epidemiological indicators, poverty and municipal inequalities persist, and these contribute to permanence of leprosy. It reinforces the importance of investments in health actions and inclusion policies, in order to minimize existing inequalities and consequently to control the endemy.